Traumatic Ulcerative Granuloma with Stromal Eosinophilia: Sinister Appearing Innocuous Lesion - Keshwar, Shashi; Raut, Toniya; Jaisani, Mehul Rajesh; Shrestha, Ashish (Birat Journal of Health Sciences, 2021)
Trauma within the oral cavity is one of the common incidence of occurrence which can be an inducer as well as propagator for wide range of oral lesion of diverse course. A unique combination of formation of granulomatous lesion with reactive eosinophilic stromal infiltration in response of trauma is “traumatic ulcerative granuloma with stromal eosinophilia (TUGSE)”. It is a reactive, infrequent, self-limiting condition of oral mucosa. The commonly involved site and the clinical presentation might click to suspect it as a lesion of oral cancer. Clinical history and examination guide through the diagnosis whereas histopathology forms the basis of the diagnosis.